# How do you solve #4-2(2+4x)=x-3#?

##### 2 Answers

See the solution process below:

#### Explanation:

First, expand the terms within parenthesis on the left side of the equation by multiplying each term within the parenthesis by the term outside the parenthesis:

Next, subtract

Now, divide each side of the equation by

#### Explanation:

Firstly, distribute the bracket.

#rArrcancel(4)cancel(-4)-8x=x-3#

#"subtract x from both sides"#

#-8x-x=cancel(x)cancel(-x)-3#

#rArr-9x=-3#

#"divide both sides by - 9"#

#(cancel(-9) x)/cancel(-9)=(-3)/(-9)#

#rArrx=1/3#

#color(blue)"As a check"# Substitute this value into the equation and if the left side equals the right side then it is the solution.

#1/3-3=1/3-9/3=-8/3larrcolor(red)" right side"#

#rArrx=1/3" is the solution"#